Welcome to Westonci.ca, your ultimate destination for finding answers to a wide range of questions from experts. Join our Q&A platform to get precise answers from experts in diverse fields and enhance your understanding. Connect with a community of professionals ready to provide precise solutions to your questions quickly and accurately.
Sagot :
Answer:
Step-by-step explanation:
a. (11x) + (22x)= 33x
b. (-6x) - (-6x) = 0
c. (-13) + (14x) - (+13t) = -13t + 14x - 13
d. (-4t) + (+4t) - (-6t) = 6t
Answer:
a. (11x) + (22x) = 33x
b. (-6x) - (-6x) = -12x
c. (-13t) + (14x) - (+13t) = (0t) + (14x)
d. (-4t) + (+4t) - (-6t) = 6t
Hope this helps! :)
We hope you found what you were looking for. Feel free to revisit us for more answers and updated information. Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We're glad you visited Westonci.ca. Return anytime for updated answers from our knowledgeable team.